The Role of Posyandu Cadres as Peer Support in Increasing MMS Consumption Compliance and Preventing Anemia in Pregnant Women - Meis Nurhayati S. Yunus; Rani Safitri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Pregnancy is a crucial period that requires special attention to maternal nutritional status, including the prevention of anemia through the consumption of Multiple Micronutrient Supplements (MMS). Compliance with MMS consumption remains a challenge due to physical, psychological, and social factors. This study aims to analyze the role of Posyandu cadres as peer support in improving compliance with MMS consumption and preventing anemia in pregnant women in the Bongo II Community Health Center, Boalemo Regency. The study used a pre-experimental one-group pretest-posttest design with a total sample of 20 pregnant women. Peer support interventions in the form of education, motivation, reminders, and routine monitoring were carried out for 4 weeks. Data were collected through questionnaires, MMS consumption records, and hemoglobin level examinations, then analyzed using the Wilcoxon test and paired t-test. The results showed a significant increase in the mean score of MMS consumption compliance from 61.2 to 80.5 (p = 0.002) and the mean hemoglobin level from 10.7 g/dL to 11.4 g/dL (p = 0.014). This finding confirms the effectiveness of peer support by Posyandu cadres in increasing compliance with MMS consumption and improving anemia status.